Managing the Muslim problem for Philippines 2000 issues and prospects - Tanggol, Sukarno D. (Philippine Journal of Public Administration, 1994)
The Muslim problem has faced the Manila government since the Spanish colonization of the islands. Many attempts have been made to settle conflicts between the national government and the Muslims, but many intended solutions do not fully meet their desired ends. The writer presents some options in accordance with the Philippines 2000 program. Through these proposals, it is hoped that Filipinos, both Christian and Muslims, can participate equally in the political process and benefit mutually from the socio-economic progress attained.